2021
DOI: 10.1111/jfpp.15313
|View full text |Cite
|
Sign up to set email alerts
|

Impact of carboxymethyl cellulose coating enriched with Thymus vulgaris L. extract on physicochemical, microbial, and sensorial properties of fresh hazelnut ( Corylus avellana L.) during storage

Abstract: In this study, the antioxidant and antimicrobial effects of carboxymethyl cellulose (CMC) enriched with Thymus vulgaris L. extract (TE) on physicochemical, microbial, and sensorial properties of fresh hazelnut were investigated. Hazelnuts treated with CMC coating solution (0.0, 0.5, and 1.5% wt/vol) containing TE (0.0, 0.5, and 1.0% vol/vol) and stored at ambient temperature for 147 days. The results showed that the uncoated sample had the highest mean moisture content (4.03%), yeast and mold count (2.63 Log c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Similarly, Razavi et al. (2021) claimed that the carboxymethyl cellulose coating enriched with thymus vulgaris extract decreased the yeast and mold count of hazelnut during 147 days of storage and the uncoated sample showed the highest amount of yeast and mold. Besides, Maghsoudlou et al.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, Razavi et al. (2021) claimed that the carboxymethyl cellulose coating enriched with thymus vulgaris extract decreased the yeast and mold count of hazelnut during 147 days of storage and the uncoated sample showed the highest amount of yeast and mold. Besides, Maghsoudlou et al.…”
Section: Resultsmentioning
confidence: 94%
“…These results are consistent with Hashemi et al (2021), which reported that the edible coating containing alginate and thyme oil reduced mold and yeast growth in fresh pistachio. Similarly, Razavi et al (2021) claimed that the carboxymethyl cellulose coating enriched with thymus vulgaris extract decreased the yeast and mold count of hazelnut during 147 days of storage and the uncoated sample showed the highest amount of yeast and mold. Besides, Maghsoudlou et al (2013) reported that the mold growth was almost zero in the pistachio nut samples that contained edible coating while it highly increased in the control sample during storage.…”
Section: Yeast and Mold Countmentioning
confidence: 97%
“…TBA value is widely used as an index for the second stage of lipid oxidation (Razavi et al, 2021). The TBA values of the soybean oil samples containing the different concentrations (100, 200, and 300 mg/kg) of the commercial and natural antioxidants during the 8 days of storage at 60°C are illustrated in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…Thiobarbituric acid value is widely used as an indicator for the second product of lipid oxidation (malondialdehyde) [38]. The thiobarbituric acid values of soybean oil samples containing different concentrations (100, 200, and 300 mg/kg) of natural antioxidants bath ultrasound extraction obtained from commercial, and were investigated during 8 days of storage at 60°C.…”
Section: Thiobarbituric Acid Valuementioning
confidence: 99%